1994
DOI: 10.1159/000282566
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens in Peyronie’s Disease

Abstract: This study presents data on HLA phenotypes of 52 unrelated patients suffering from idiopathic Peyronie’s disease. This first investigation on HLA class II antigens detected an association of HLA-DR3 and -DQw2 in this disorder. HLA typing was done from ACD-stabilized peripheral blood using the modified lymphocytotoxicity test. Antigen frequencies of the patient group were compared with those of healthy individuals of the local population. There were no deviations of frequencies for antigens of the B7 cross-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
0
12
0
7
Order By: Relevance
“…They found a positive correlation only with HLA B27 and concluded that, because none of the bacterial cultures were positive, molecular mimicry or infection was not responsible for PD. 27 Rompel et al 12,13 performed HLA typing on 52 unrelated individuals with PD using a modi®ed lymphotoxicity test for both class I and II MHC. They found a statistically signi®cant association with HLA A1 and HLA DQw2, and in their 1994 study, they reported an association with HLA B8, Cw7 and DR3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a positive correlation only with HLA B27 and concluded that, because none of the bacterial cultures were positive, molecular mimicry or infection was not responsible for PD. 27 Rompel et al 12,13 performed HLA typing on 52 unrelated individuals with PD using a modi®ed lymphotoxicity test for both class I and II MHC. They found a statistically signi®cant association with HLA A1 and HLA DQw2, and in their 1994 study, they reported an association with HLA B8, Cw7 and DR3.…”
Section: Discussionmentioning
confidence: 99%
“…The ®rst two reports that demonstrated a positive association evaluated only 17 patients combined, 30,33 but two other studies, evaluating 80 patients, 10,13 failed to demonstrate a positive association. With respect to class II MHC, only Rompel 13 reported an association. 25 In a study of 31 males, Nachtsheim and Rearden 11 reported an association with HLA DQ5.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chilton et al [3] and Hinman [15], it has been associated with a generalized fibrotic tendency, so accompanying diseases have been investigated up to now. Recently, Rompel et al [14] studied the involvement of autoimmune factors in Peyronie's disease, and reported an association between class I and II HLA antigens and Peyronie's disease. They also noticed a common haplotype related with these antigens in Peyronie's disease.…”
Section: Discussionmentioning
confidence: 99%
“…This haplotype has been associated with numerous autoimmune disorders and is also increased in insulindependent diabetes. It has therefore been suggested that Peyronie's disease may be due to an autoimmune disorder and may also have an inherited predisposition similar to other autoimmune diseases [13,14]. Nyberg et al [16] reported father-to-son transmission of Peyronie's disease and Dupuytren's contracture in three generations and suggested that this was an autosomal dominant trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation